2021
DOI: 10.2147/jir.s324336
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Significance of the HHLA2 Protein in Hepatocellular Carcinoma and the Tumor Microenvironment

Abstract: Background The protein “human endogenous retrovirus H long terminal repeat-associating 2” (HHLA2), a member of the B7 family, has been linked to cancer progression and immune responses. However, its functional role in hepatocellular carcinoma (HCC) remains unknown. Methods Bioinformatics was used to examine the potential roles of HHLA2 in HCC and the molecular pathways involved. Expression of HHLA2 and PD-L1 as well as the density of tumor-infiltrating lymphocytes (TILs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
5
22
0
Order By: Relevance
“…In the present report, our results showed that high HHLA2 expression was correlated with poor OS in five tumors, including KICH, LAML, LIHC, and PAAD. Similarly, it was previously reported that HHLA2 expression was linked to shorter survival time in patients with clear cell renal cell carcinoma [ 7 ], gastric cancer [ 28 ], and hepatocellular carcinoma [ 29 ]. By contrast, high HHLA2 expression is predictive of a good prognosis in patients with BLCA, KIRC, READ, and SKCM.…”
Section: Discussionmentioning
confidence: 72%
“…In the present report, our results showed that high HHLA2 expression was correlated with poor OS in five tumors, including KICH, LAML, LIHC, and PAAD. Similarly, it was previously reported that HHLA2 expression was linked to shorter survival time in patients with clear cell renal cell carcinoma [ 7 ], gastric cancer [ 28 ], and hepatocellular carcinoma [ 29 ]. By contrast, high HHLA2 expression is predictive of a good prognosis in patients with BLCA, KIRC, READ, and SKCM.…”
Section: Discussionmentioning
confidence: 72%
“…However, HHLA2 can also bind to another inhibitory receptor, three immunoglobulin domains and long cytoplasmic tail 3 (KIR3DL3), which inhibits T cell action (16). In terms of cancer, higher expression levels of HHLA2 were previously reported to be associated with poorer prognoses or higher degrees of tumour invasion in lung carcinoma, hepatocellular carcinoma and prostate cancer (17)(18)(19). By contrast, in epithelial ovarian cancer, higher HHLA2 expression levels were demonstrated to be associated with superior survival outcomes and reduced tumor growth (20).…”
Section: Introductionmentioning
confidence: 99%
“…In HCC, iTLSs are related to a good prognosis and can reduce the risk of early recurrence of HCC. Moreover, the upregulation of iTLS-related genes can also reduce the risk of HCC recurrence in the early and middle stages, which indicates that iTLS may be related to the existence of sustained and effective anti-tumor immunity (49,(61)(62)(63)(64). In addition, the risk of HCC recurrence is also related to TLS maturity (primary or secondary follicles and lymphoid aggregates) (61,64).…”
Section: Role Of Itls In Phcmentioning
confidence: 99%